2022
DOI: 10.1002/ps.6981
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of novel rost‐4‐ene derivatives as potential plant activators for preventing phytopathogenic bacterial infection: Design, synthesis and biological studies

Abstract: BACKGROUND Gradually aggravated disease caused by phytopathogenic bacteria severely restricts food security and crop yield, and few pesticides can relieve this severe situation. Thus, development and excavation of new agrochemicals with high bioactivity and novel action mechanism may be a feasible strategy to control intractable bacterial diseases. As a privileged molecular framework, steroid molecules exhibit diversiform bioactivities. Herein, a series of novel androst‐4‐ene derivatives were designed, synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…In order to determine the structure–activity relationships (SARs) of the title compounds, the title compounds were further modified according to the following four schemes: (a) rigid and saturated aliphatic amines were replaced with variably flexible benzylamines groups; (b) the p -dioxybenzene group was substituted with a m -dioxybenzene, o -dioxybenzene, or piperazinyl group; (c) the antibacterial efficiency of optimized molecules was examined after removal of hydroxyl or isopropanolamine groups; and (d) substituent groups (−Cl, −F, or −OCH 3 ) were introduced into the 4- or 6-position of the benzothiazole pharmacophore. Finally, the antibacterial activity of the 53 newly synthesized compounds was screened against three plant pathogen strains ( Xoo , Xac , and Psa ) using the turbidimetric method …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to determine the structure–activity relationships (SARs) of the title compounds, the title compounds were further modified according to the following four schemes: (a) rigid and saturated aliphatic amines were replaced with variably flexible benzylamines groups; (b) the p -dioxybenzene group was substituted with a m -dioxybenzene, o -dioxybenzene, or piperazinyl group; (c) the antibacterial efficiency of optimized molecules was examined after removal of hydroxyl or isopropanolamine groups; and (d) substituent groups (−Cl, −F, or −OCH 3 ) were introduced into the 4- or 6-position of the benzothiazole pharmacophore. Finally, the antibacterial activity of the 53 newly synthesized compounds was screened against three plant pathogen strains ( Xoo , Xac , and Psa ) using the turbidimetric method …”
Section: Resultsmentioning
confidence: 99%
“…are particularly intractable, as exemplified by Xanthomonas oryzae pv oryzae ( Xoo ), which is ranked fourth among the top 10 most important plant pathogenic bacteria. Xoo causes rice bacterial leaf-blight disease, which can diminish rice production by 20–80%. , Although several commercial pesticides are currently used to control rice bacterial leaf-blight disease, including bismerthiazol (BT), streptomycin, and amobam, emerging pesticide resistance has reduced their control efficiency. Therefore, the need for new agrochemicals exhibiting novel antibacterial modes of action has sparked considerable research interest.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the in vitro bioassays, the active compound 9a (afforded with the lowest EC 50 value of 12.85 μg/mL toward Psa ) was chosen to assess the in vivo anti- Psa activity via the pot experiment [ 47 , 48 , 49 ]. The results ( Table 4 ) showed that compound 9a presented commendable protective and curative activities against kiwifruit bacterial canker at 200 μg/mL with control efficiencies of 46.05% and 32.89%, respectively, which were much better than those of the commercial bactericide TC (31.58% and 17.11%, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…The minimum bactericidal concentration (MBC) of the three kinds of nanoparticles was 1.56 μg/mL, which was much lower than that of thiodiazole copper (MBC > 100 μg/mL, Figure S4 ). Compared with the antibiotics [ 51 ], natural compounds [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ], and synthetic compounds [ 18 , 19 , 20 , 21 , 22 , 23 ] reported in the literature, copper-based nanoparticles also have advantages in bactericidal performance. The antibacterial mechanism of copper-based nanoparticles may be related to their compositions, morphologies, and sizes [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many novel compounds or methods have been developed to control kiwifruit bacterial canker, including natural products [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ], synthetic organic compounds [ 3 , 18 , 19 , 20 , 21 , 22 , 23 ], copper complexes [ 24 , 25 ], sulfur [ 26 ], bacteriophages [ 27 , 28 , 29 ], and other biological control agents [ 30 , 31 ]. These methods exhibited excellent control efficacies for kiwifruit bacterial canker.…”
Section: Introductionmentioning
confidence: 99%